GENDER DALAM KONSUMSI MEDIA MASSA - Akil, Rafiuddin (FISIP IBI-K57 Prodi Komunikasi, 2020)
Television was one of mainstream mass media which people still uses for their information needs. People will follow and gives reference to act learning from television conten. Gender was a social context to descripe compare man and women in information consumption behaviour for television. The purpose of this research is to look at the level of gender differences in the behavior of consuming mass media, especially talk shows Hotman Paris Show on iNews television. This research uses the uses and gratification theory from Palmgreen and Rosengreen (1985) model. The research method with a quantitative approach, with chi square test hypotesis. The sample used was 80 students at a campus in Jakarta with simple random sampling. The results showed no difference in behavior after consuming information talk shows Hotman Paris Show on iNews television between men and women. The element most seen in talk shows on television is education. Dominant behavior that arises after watching a talk show on television shows is cognitive or shows only affect the minds of the people.